Rekonsiliasi Sejati: Menjumpakan Pesan Perdamaian melalui Tradisi Na Tek Oko bagi Masyarakat Suku Timor - Firman Panjaitan; Jufantri Leo (TEVUNAH: Jurnal Teologi dan Pendidikan Kristen, 2023)
Peace is one of the basic needs of human life. Every tribe and nation strives for equilibrium to be realized so that life can be perpetuated. One of the cultures in Timorese society to strive for peace is the Na Tek Oko tradition. Through this tradition, each person or tribe at war will be reconciled by sitting and eating betel nuts together in a happy atmosphere. Sitting together signifies that both parties are equal and equal so that peace efforts can be made. This parallels what God did when He reconciled Himself with humans, namely by humanizing Himself to become neighbours for humans. Using qualitative methods, especially literature studies and open interviews with traditional Timorese leaders, it was found that the Na Tek Oko tradition, in essence, parallels the Bible's message, especially regarding the atonement that God made for humans. Thus the Na Tek Oko tradition can be used as contextual theology to build peace in Timorese society.